OVIPOSITION PREFERENCE OF TWO SPECIES OF PSYLLID (CARDIASPINA ALBITEXTURA AND CARDIASPINA RETATOR) ON EUCALYPTUS CAMALDULENSIS LEAVES - Nismah . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2005)
Oviposition preference of two species of psyllid (Cardiaspina albitextura and Cardiaspina retator) on Eucalyptus camaldulensis leaves. Study on oviposition preference of two species of psyllid (Cardiaspina albitextura and Cardiaspina retator) on Eucalyptus camaldulensis was conducted in open area around Bundoora Campus, La Trobe Univesity, Australia. The purpose of this study was to examine the oviposision preference of two difference species of psyllid. Seven E. camaldulensis trees occupied by both C. albitextura and C. rotator were chosen. Leaves of E. camaldulesis were sampled in two periods of oviposition. Four E. camaldulensis trees labelled with t1, t2, t3 and t4 were sampled in period of oviposition I and seven trees in period of oviposition II (4 trees were same as trees in period I ( t1, t2, t3, t4 and 3 other trees t5, t6 and t7 ). Thirty randomly selected leaves, occupied by the eggs of both C. albitextura and C. rotator, were taken from each tree. The samples of leaves were brought to laboratory to examine the eggs on each side (adaxial and abaxial) of leaves. The eggs were counted under 10 x magnifications and recorded. Correlation was used in the data analysis and significance of r-value was tested by t test. The result indicated that both species of pest (C. albitextura and C. rotator) chose the same side of leave for oviposition. Both C. albitextur and C. retator prefer the abaxial surface of leaves to oviposit on most trees sampled in the field. The numbers of eggs oviposited by C. albitextur had a positive correlation with the number of eggs oviposited by C. retator. The number of eggs laid by both species depended on period of ovipositon, tree, and side where the eggs were laid.